Infecção natural por Sarcocystis spp. em gatos do sul do Brasil: desenvolvimento de cistos musculares, epidemiologia e soroprevalência - Lucio, Bruna Marquardt (2019)
Sarcocystis spp. are protozoa belonging to the phylum Apicomplexa capable of infecting a wide variety of animals. Among the several species from the genus Sarcocystis, there is a remarkable variability in relation to the involved hosts, however, the formation of tissue cysts in the intermediate host is an inherent characteristic of all species of this protozoan. Domestic cats are classically recognized as definitive hosts for certain species of Sarcocystis, but recent studies show that these animals play a role as natural intermediate host (IH) for S. felis and S. neurona. Some cats have developed central nervous system (CNS) infection due to S. neurona. In the majority of cases, S. neurona was the species involved and the animals developed severe neurologic signs. In Brazil, the importance of the domestic cat as natural IH for any species of Sarcocystis remains unknown. Based on this, it is important to investigate the occurrence of Sarcocystis spp. in Brazilian domestic cat tissues, in order to verify if these animals can act as natural IH for some species of Sarcocystis in our territory. Therefore, this study aims to evaluate the presence of muscle sarcocysts in cats submitted to necropsy with subsequent identification of the involved species and to evaluate the seroprevalence of Sarcocystis spp. in the feline population of Southern Brazil as well. To verify the presence of muscle sarcocysts, 100 cats submitted to routine necropsy had fragments of certain muscle groups collected for histological analysis and polymerase chain reaction (PCR). Epidemiological data (gender, age, race and reproductive status) and information associated with previous use of drugs with immunosuppressive potential, feline immunodeficiency virus (FIV)/feline leukemia virus (FeLV) infection status and outdoor access were collected from the clinical history. The cause of death or reason for euthanasia was obtained through the autopsy report. Positive histology and PCR positive cases were referred for genetic sequencing. Additionally, sera from 497 cats attending to the Hospital Veterinário Universitário (HVU) were submitted to the indirect fluorescence antibody test (IFAT) technique for antibodies anti-Sarcocystis spp. detection. Of the 100 cats analyzed, 5 (5/100; 5%) had muscular sarcocystosis and the only species involved in all cases was confirmed as S. neurona by PCR. In the serological analysis, 24 cats (24/497; 4.82%) presented anti-Sarcocystis spp antibodies. Our results confirm that Sarcocystis spp. circulates among the studied feline population and confirm that domestic cats are able to play a role as natural intermediate host for S. neurona. Our study aids to what is already known concerning natural S. neurona infection in cats. Additionally, S. neurona should be considered a differential diagnosis in cases of CNS involvement in cats in our region.